CLINICAL AND PATHOPHYSIOLOGICAL SUBSTANTIATION OF THE MUTUAL AGGRAVATION SYNDROME IN COMBINED COMBAT THERMOMECHANICAL INJURY - Korol, S.O.; Chelishvili, A.L.; Palii, I.P.; Musenko, O.Ya.; Svystak, N.V. (World of Medicine and Biology, 2023)
There was a comparative integrated clinical examination of 93 persons with combined combat thermomechanical injuries, 87 persons with isolated extremity injuries involving bone fractures and 65 persons with isolated burn injuries. The said examination covered the recording of integral body rheography, study of coagulation tests results, biochemical, immunological blood indicators at admission on 1–3 and 5–7 days after the injury. The authors believe that only persons with extremely severe combined combat thermomechanical injuries, when there are two or more isolated injuries (wounds and burns), experience severe homeostasis disorders, which is demonstrated by the mutual aggravation syndrome with central hemodynamics as the leading link in its pathogenesis.
Keywords: mutual aggravation syndrome; combined combat thermomechanical injuries; shock